2011
DOI: 10.1088/0004-637x/743/1/21
|View full text |Cite
|
Sign up to set email alerts
|

CONSTRAINTS ON THE UNIVERSAL C IV MASS DENSITY ATz∼ 6 FROM EARLY INFRARED SPECTRA OBTAINED WITH THE MAGELLAN FIRE SPECTROGRAPH

Abstract: We present a new determination of the intergalactic C iv mass density at 4.3 < z < 6.3. Our constraints are derived from high signal-to-noise spectra of seven quasars at z > 5.8 obtained with the newly commissioned Folded-Port Infrared Echellette (FIRE) spectrograph on the Magellan Baade telescope, coupled with six observations of northern objects taken from the literature. We confirm the presence of a downturn in the C iv abundance at z = 5.66 by a factor of 4.1 relative to its value at z = 4.96, as measured … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 47 publications
(75 reference statements)
6
91
0
Order By: Relevance
“…It is also relatively straightforward to model because it arises in gas that is optically thin to ionizing photons and lies far enough away from galaxies that the local radiation field may be neglected to first order. Its overall mass density is robustly observed to decline slowly with increasing redshift (Songaila 2001;Becker et al 2009;Ryan-Weber et al 2009;D'Odorico et al 2010D'Odorico et al , 2013Simcoe et al 2011;Becker et al 2011;Cooksey et al 2013). Numerous studies have shown that the observed decline can readily be accommodated by numerical simulations (Oppenheimer & Davé 2006;Oppenheimer et al 2009;Cen & Chisari 2011).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is also relatively straightforward to model because it arises in gas that is optically thin to ionizing photons and lies far enough away from galaxies that the local radiation field may be neglected to first order. Its overall mass density is robustly observed to decline slowly with increasing redshift (Songaila 2001;Becker et al 2009;Ryan-Weber et al 2009;D'Odorico et al 2010D'Odorico et al , 2013Simcoe et al 2011;Becker et al 2011;Cooksey et al 2013). Numerous studies have shown that the observed decline can readily be accommodated by numerical simulations (Oppenheimer & Davé 2006;Oppenheimer et al 2009;Cen & Chisari 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Intergalactic C IV and C II absorbers are observed along sightlines to quasars out to the highest redshifts probed (Songaila 2001;Ryan-Weber et al 2006;Becker et al 2009;Ryan-Weber et al 2009;Simcoe et al 2011;D'Odorico et al 2013;Becker et al 2011). They occur naturally in cosmological hydrodynamic simulations in which galactic outflows expel metals out to the virial radius and beyond (Theuns et al 2002;Cen et al 2005; Oppenheimer & Davé 2006, 2008Oppenheimer et al 2009;Cen & Chisari 2011), opening up the possibility of using models to interpret them as tracers of star formation, outflows, and the ultraviolet ionizing background (UVB).…”
Section: Introductionmentioning
confidence: 99%
“…To account for the decreasing sensitivity to lower column densities, authors using automatic line identification methods may also assume a constant path length across all column densities and employ Monte Carlo completeness corrections (e.g., Simcoe et al 2011) in the derived statistics. Our survey comprises a visually identified absorber sample, and the method presented here alternatively measures a variable path length from the data S/N; the two methods should produce consistent results.…”
Section: Path Length Calculationmentioning
confidence: 99%
“…The C IV absorbers at z=5-6 were selected from the sample of Simcoe et al (2011). From this sample, we select four secure, strong C IV absorbers at z=4.87-5.74 in two QSO sightlines: SDSS J1030+0524 (z QSO =6.30) and SDSS J1306 +0356 (z QSO =6.00).…”
Section: Sample Selectionmentioning
confidence: 99%